Numerical analysis of laminar pulsating flow at a backward facing step with an upper wall mounted adiabatic thin fin - Sehmefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2013)
The effect of an upper wall mounted adiabatic thin fin on laminar pulsating flow in a backward facing step has been investigated numerically. Study is performed for different Reynolds numbers (based on the step height) in the range of 10 and 200 and for the expansion ratio of 2. The working fluid is air with the Prandtl number of 0.71. The governing equations are solved with a general purpose finite volume based solver, FLUENT. The effects of various pertinent parameters, Reynolds number, fin length and pulsating frequency on the fluid flow and heat transfer characteristics are numerically studied. It is observed that fin alters the flow field and thermal characteristics. In the steady flow case, heat transfer enhancement is obtained with the installation of the fin on the upper wall and increases with increasing fin length and increasing Reynolds number. Heat transfer enhancement of 188% is obtained for fin length of L-f = 1.5H at Reynolds number of 200. In the pulsating flow case, time-spatial averaged Nusselt number along the bottom wall downstream of the step normalized with spatial averaged Nusselt number in the steady flow case versus excitation Strouhal number shows a resonant type behavior; first an increase in the value is seen up to St = 0.05, then a decrease is seen with the increasing values of the frequency of the pulsation for the case without fin. Adding a fin shifts the maximum value of the normalized Nusselt number from St = 0.05 to St = 0.1. Compared to steady flow with no-fin case, adding a fin is not advantageous for heat transfer enhancement in pulsating flow. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Pulsating flow; Adiabatic fin; Backward facing step